Personality and regional innovativeness: An empirical analysis of German patent data - Leonie Reher; Petrik Runst; Jörg Thomä (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2022)
This paper contributes to the new literature on the role of personality for regional innovativeness by examining whether this role varies between different types of regions. Building on regionally aggregated levels of individual Big Five personality traits, we find that only extraversion has a positive effect on patenting in German regions. Its impact is particularly important in lagging regions. We interpret this result as an indication of the compensatory role of collaboration for the innovativeness of lagging regions characterized by low levels of (business) R&D, which demonstrates the need for place-sensitive policies that take into account different modes of innovation.
Keywords: J24; O18; O30; R1; 330; Innovation; Big Five; Personality; Lagging regions